Could there be any relationship between nutritional deficiencies and idiopathic chest pain in children? - Kayalı, Şeyma; Belder, Nuran; Gürlek Gökçebay, Dilek (The European Research Journal, 2019)
Objectives: Chest pain in childhood is a frequent cause of referral to pediatric cardiology departments although cardiac etiology is very rare. Etiology is usually unidentified and named as ‘idiopatic chest pain’. It is also well known fact that chronic pain is associated with insuffiency of some nutritional factors even in childhood. Our aim was to investigate if there is a relationship between nutritional defiencies with idiopathic chest pain in children.Methods: We retrospectively reviewed 364 patients who were referred pediatric cardiology department in one year period due to experienced chest pain more than one time. Among these patients, a total of 109 patients who had complete blood count, serum ferritin, vitamin B 12 and 25-(OH) vitamin D levels in pediatric outpatient clinics before and the etiology was still unidentified after a detailed cardiac and other examinations formed the study group. Age and sex matched 59 healthy children without chest pain formed the control group. All participants had been evaluated with a detailed physical examination and patients in chest pain group also had an electrocardiographic ve echocardiographic evaluation.Results: Vitamin B12 and Vitamin D levels were lower in noncardiac chest pain group while there was no difference between groups in term of ferritin levels and complete blood count parameters. These difference is statistically significant particularly in vitamin D levels.Conclusions: Our results showed that low Vitamin D levels is associated with chronic chest pain in children. The present study provide the necessity of evaluating nutritional parameters in  children with noncardiac chest pain.